Lynch Company's River Navigation Franchises in Mesopotamia: Economic Control and Local Responses 1860-1908 - Qader, Ali Mohammed (Journal of Humanities & Social Sciences, 2024)
During the 19th century, the advantageous geographical position of Mesopotamia and its access to river transportation via the Tigris and Euphrates rivers drew the attention of foreign enterprises, notably the British, as the Ottoman State's power declined. The British enjoyed privileges in trade and navigation, leading to limited domestic production and imported goods. They focused on transportation routes, oil resources, and defending its commercial interests in the Middle East. They established a railway project, gaining diplomatic immunity and privileges in river navigation. The British Lynch Company's River Navigation franchises in Mesopotamia from 1860 to 1908 were significant. This research examines the historical significance and outcomes of these franchises, focusing on the economic control strategies used by the company and the reactions of the local population. The study found that British companies, like the Lynch Company, took advantage of trade benefits, leading to a dependence on imported commodities and limited local manufacturing. Moreover, the British steamships, particularly those operated by the Lynch Company, had a dominant position in river trade in Basra. Britain's desire for Mesopotamia was motivated by geopolitical, economic, and political factors, such as protecting transit lines and countering competing forces from France and Russia. The use of steam power transformed transportation by replacing sailing vessels and facilitating swifter river traffic. Further research should explore the societal and ecological impacts of British business endeavours in Mesopotamia during this time frame. Additional study should investigate the wider societal and ecological impacts of British business endeavours in Mesopotamia during this time frame. Examining how local communities react to foreign economic dominance may provide valuable insights into the wider historical backdrop and its effects on regional progress. This research enhances our knowledge of the intricate economic patterns throughout colonial times and their long-lasting effects in the Middle East.
Keywords: Britain; Franchises; Lynch Company; Mesopotamia; Ottoman Empire; River Navigation